1969
DOI: 10.1364/ao.8.000447
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aerosol Size Distribution from Spectral Attenuation Measurements

Abstract: A method of evaluating the aerosol size distribution from the spectral attenuation measurements is shown. The process consists of solving the simultaneous integral equations, and examples are given of solutions based on the attenuation measurements made by Knestrick et al. over the Chesapeake Bay. It is found that the evaluated individual size distributions do not necessarily follow the power law, although departures from it are mostly small. If the power law is to be adopted neglecting small departures, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(61 citation statements)
references
References 12 publications
3
57
0
1
Order By: Relevance
“…Accurate spectral measurements of the optical thickness both for stratospheric and tropospheric aerosols are efficient means of and highly desirable in constructing reasonable optical models of aerosols. Yamamoto and Tanaka (1969) and King et al (1978). They The wavelength range of input data *a(*)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate spectral measurements of the optical thickness both for stratospheric and tropospheric aerosols are efficient means of and highly desirable in constructing reasonable optical models of aerosols. Yamamoto and Tanaka (1969) and King et al (1978). They The wavelength range of input data *a(*)…”
Section: Discussionmentioning
confidence: 99%
“…1. Assuming that aerosols are homogeneous, spherical particles, size distributions of total aerosols in the vertical air column can be estimated by means of the socalled inversion method from spectral optical thickness measurements (e. g., King et ai.1978 ;Yamamoto and Tanaka, 1969). The inversion method is discussed in detail in Appendix.…”
Section: Characteristics Of Aerosol Size Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the inversion to the refractive index has been investigated by Yamamoto and Tanaka (1969) and King et al (1978). They showed that the inverted size distributions maintain their shape for small changes in the complex refractive index.…”
Section: Estimation Of the Aerosol Size Distribution (A) Troposphericmentioning
confidence: 99%
“…Atmospheric aerosols affect on climate through radiative transfer process as well as microphysical process in cloud formation. As for the former, many researchers have reported about the absorption properties of atmospheric aerosol particles, since the atmospheric aerosols is greatly affected by the imaginary term of the refractive index (Lm(m *)) imaginary term of the refractive index (Im(m*)) (Yamamoto and Tanaka, 1972). However, the complex refractive indices of the atmospheric aerosols have not yet known well, even though various techniques have been proposed (Gerber and Hindman,1982).…”
Section: Introductionmentioning
confidence: 99%